Flow in non-gradient channel with turbulators. - Терещенко, Ю. М.; Дорошенко, К. В. (Science-based technologies, 2011)
The research results of turbolators influence on the mixing intensity in the boundary layer of non-gradient channel are presented in the article. The estimation of influence of turbolators on the ideal mixing process was carred out by means of flow numerical simulation. Comparison results of numerical and physical experiments are given.